Characterization and technological properties of lactic acid bacteria isolated from traditional Argentinean goat’s milk products - Taboada, Natalia Verónica (2014)
A total of 286 lactic acid bacteria isolated from goat’s dairy products in northwest of Argentina were characterized. Lactobacilli (38%) and cocci (62%) were identified according to morphological, physiological, and relevant technological properties. L. plantarum (14%) and Enterococcus (34%) were the predominant species. S. thermophilus, Pediococcus and L. plantarum were the highest acid producers. Eight strains of L. fermentum produced bacteriocins or metabolites similar to bacteriocins. The API-ZYM test was applied to 39 isolates. Eight strains were selected from their both technological properties and enzymatic activities for use as starter or adjunct culture in the manufacture of artisanal goat cheeses.